PERAN COVID 19 DALAM MEMEDIASI KECEMASAN TERHADAP STRES KERJA - Fadli, Ahmad -; Sinaga, Anggiat (Universitas Islam Syekh-Yusuf, 2021)
The purpose of this study was to determine the effect of anxiety on covid 19 and its impact on employee work stress. The approach in this research is associative. The population and sample in this study were 70 employees at Kumala Hotel Banda Aceh. While the sampling technique used a saturated sample. Data analysis using path analysis. The results showed that anxiety had a positive and significant effect on covid 19. Then anxiety and covid had no effect on employee work stress. Finally, covid 19 has a role in mediating anxiety about employee work stress.